2013
DOI: 10.1038/clpt.2013.12
|View full text |Cite
|
Sign up to set email alerts
|

International Transporter Consortium Commentary on Clinically Important Transporter Polymorphisms

Abstract: This Commentary focuses on genetic polymorphisms in membrane transporters. We present two polymorphisms for which there is a compelling body of literature supporting their clinical relevance: OATP1B1 (c.521T>C, p.V174A, rs4149056) and BCRP (c.421C>A, p.Q141K, rs2231142). The clinical evidence demonstrating their role in variation in pharmacokinetics and pharmacodynamics is described along with their allele frequencies in ethnic populations. Recommendations for incorporating studies of transporter polymorphisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
144
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(146 citation statements)
references
References 10 publications
1
144
1
Order By: Relevance
“…We did not find this polymorphism to affect rifabutin exposure; however, our study included insufficient carriers of this polymorphism to exclude an association. While rs4149056 is more frequent in Asian and Caucasian populations than in other populations, the low frequency of this SNP in our study (Table 1) is consistent with the reported population frequency (0.7 to 11.5%) in sub-Saharan Africa (21).…”
supporting
confidence: 80%
“…We did not find this polymorphism to affect rifabutin exposure; however, our study included insufficient carriers of this polymorphism to exclude an association. While rs4149056 is more frequent in Asian and Caucasian populations than in other populations, the low frequency of this SNP in our study (Table 1) is consistent with the reported population frequency (0.7 to 11.5%) in sub-Saharan Africa (21).…”
supporting
confidence: 80%
“…The assessment of OATP1B-mediated DDIs with certain chemotypes (e.g., anionic small molecule drug candidates) has become a critical aspect of early drug development as recognized in draft guidance issued by the regulatory agencies in the United States (U.S. Food and Drug Administration Center for Drug Evaluation and Research, 2012; http:// www.fda.gov/downloads/drugs/guidancecomplianceregulatoryinformation/ guidances/ucm292362.pdf), the European Union (Committee for Human Medicinal Products, 2012; http://www.ema.europa.eu/docs/en_GB/ document_library/Scientific_guideline/2012/07/WC500129606.pdf) and the International Transporter Consortium (Giacomini et al, 2013;Tweedie et al, 2013). These guidance documents/perspectives acknowledge OATP1B1 and OATP1B3 as two of the seven clinically relevant transporters and provide basic methodology toward the prediction of the DDI magnitude with OATP inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of DDI arising via inhibition for OATP1B1-mediated hepatic uptake (R value) by FA was calculated using eq. 7 (Giacomini et al, 2013;Tweedie et al, 2013): where K i would represent the inhibition constant for OATP1B1 by FA and I in, max,u represents the estimated maximum unbound FA concentration at the inlet to the liver and is defined as follows (Ito et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Such observations also suggest that interindividual differences in BCRP function due to pharmacogenetics likely contribute to variability in bioavailability (absorption), exposure [area under the plasma concentrationtime curve (AUC) and maximum plasma concentration (C max )], and efficacy of drugs that are BCRP substrates (Giacomini et al, 2010(Giacomini et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…The important role that BCRP plays in drug disposition has been demonstrated clinically in pharmacogenetic studies investigating the ABCG2 single nucleotide polymorphism c.421C.A (Q141K, rs2231142), in which the impaired transport function phenotype (421CA or AA) resulted in increased plasma exposures of several BCRP substrate drugs, including rosuvastatin, atorvastatin, fluvastatin, and diflomotecan (Sparreboom et al, 2004;Keskitalo et al, 2009;Giacomini et al, 2013). Such observations also suggest that interindividual differences in BCRP function due to pharmacogenetics likely contribute to variability in bioavailability (absorption), exposure [area under the plasma concentrationtime curve (AUC) and maximum plasma concentration (C max )], and efficacy of drugs that are BCRP substrates (Giacomini et al, 2010(Giacomini et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%